Strategi Lazismu Kota Medan dalam Penyebaran Zakat, Infaq, dan Sedekah - Zein, Gilang Hardian; Hasibuan, Wildan Ansori; Dongoran, Rita Ul-Hanifah; Nasution, Muhammad Asnawi (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2025)
Zakat, Infaq and Alms (ZIS) is an important instrument in Islam for the redistribution of wealth to achieve social welfare. However, its management in Medan City still faces big challenges. This research uses a qualitative approach based on literature studies to explore the ZIS collection and distribution strategy by Lazismu in Medan City. Analysis shows that strategies such as CSR programs, small-scale philanthropy, and the use of social media and digital applications have increased the effectiveness of ZIS management. The findings also highlight the role of technology in increasing the number of muzakki by up to 25% and expanding distribution reach. Main obstacles such as the lack of valid mustahik data and the digital divide require solutions based on technological innovation and collaboration between institutions. This research recommends strengthening digital infrastructure and public education to support the optimization of ZIS management by Lazismu in the city of Medan. Thus, a sustainable strategy can increase the role of ZIS in economic empowerment and community welfare.